(untitled) (Journal of Faculty of Education, 2021)
The scientific paper aimed to identify the Physics misconceptions in the first year book of the secondary school stage, and the extent of their effective to the students’ subsequent learning. The descriptive and the experimental methods were followed, that, with the book content analysis, and an application of pre and post tests, to discover the misconceptions effect to the subsequent learning. The sample were the fourth year Physics students, at the Faculty of Education – Khartoum university, which contains 24 students, chosen with an intention method. A pre test was conducted, then the corrigenda were done, and a post test was conducted. The statistical analysis program (SPSS) was used to analyze the data. The scientific paper comes out to the following results: There are scientific misconceptions in the first year Physics book at the secondary instruction stage. The use of different methods of teaching, help in the correction of the Physics misconceptions, which students acquired. Students learning to the misconceptions, affect their subsequent learning. The percentage of misconceptions frequency to some Physics conceptions varied to the students with a large degree. The paper recommended that: the revision of Physics teacher rehabilitation and training system, and to follow the scientific methods in how toauthoring the Physics books at the secondary school stage, and specialists should participate in preparing the scientific syllabuses.